KEBIJAKAN NEP ( NATIONAL ECONOMIC PLANING) PEMERINTAHAN IRAN PADA MASA KEPEMIMPINAN PRESIDEN MAHMUD AHMADINEJAD - Tonida, M. Martin; Pahlawan, Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research is the political economy of the country of Iran in the Middle East region areexperiencing economic-political dynamics of interest in the era of Mahmud Ahmadnejad leadership.Under his leadership, Iran is trying to not be dragged into the political hegemony of internationalmainstrem dominated by the United States and its Allies. To show the existence in the context of domesticand international, Mahmoud Ahmadinejad then launched a program of the National Economic Planning(NEP).This research used a descriptive analytical methodology, while the data collection techniquesused are library research. Then the theory is used to answer the formulation / identification problem is aconstructivist approach that collaborated with the country's development theory to the achievement of theNEP.Efforts / Policies are on the run to achieve the NEP program under the leadership of MahmoudAhmadinejad of Iran has brought progress and fundamental changes to the economic and political Iran.Keyword:National EkonomicPlaning Iran The Political Hegemoni, and Mainstrem.